2023
DOI: 10.14366/usg.22078
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of the learning curve cumulative summation test to evaluate a practicum for endometrial cancer ultrasound staging

Abstract: The learning curve cumulative summation (LC-CUSUM) test is commonly used as a quantitative assessment of the individual learning process. This study aimed to evaluate the skill acquisition process for performing ultrasound staging of endometrial cancer using the LC-CUSUM test. Methods: Sixty-seven ultrasound examinations performed by two operators were evaluated using the LC-CUSUM test according to their rate of success or failure to correctly stage myometrial invasion, serosa involvement, and pelvic and para-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…We have shown that adequate skills for assessing myometrial infiltration in women with endometrial cancer may be acquired by interpreting two-dimensional real-time videoclips. Our data are in agreement with those reported by Xholli and colleagues [16]. These authors evaluated the learning curve for transvaginal ultrasound assessment of myometrial infiltration in women with endometrial cancer in a retrospective study.…”
Section: Interpretation Of Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We have shown that adequate skills for assessing myometrial infiltration in women with endometrial cancer may be acquired by interpreting two-dimensional real-time videoclips. Our data are in agreement with those reported by Xholli and colleagues [16]. These authors evaluated the learning curve for transvaginal ultrasound assessment of myometrial infiltration in women with endometrial cancer in a retrospective study.…”
Section: Interpretation Of Resultssupporting
confidence: 93%
“…In fact, performance after training should be tested in a real-time stetting. Nevertheless, data from the study of Xholli and colleagues indicated that a similar number of cases were needed to achieve competence using apparently real-time examination (around 30 cases [16]), and, as stated above, the use of offline training has been demonstrated as a valid tool for training [21,22].…”
Section: Strenthgs and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, there are numerous publications studying the importance of training programs and the implementation of standardized techniques to evaluate MI in EC via TVS in order to achieve an improvement in diagnostic accuracy 30–32 . Xholi et al 31 conducted a retrospective study in order to evaluate the learning curve for TVS assessment of MI in women with EC. Sixty‐seven real‐time ultrasound scanning examinations performed by two expert examiners were assessed using the learning curve cumulative summation (LC‐CUSUM) test.…”
Section: Discussionmentioning
confidence: 99%
“…27 Green et al 28 Recently, there are numerous publications studying the importance of training programs and the implementation of standardized techniques to evaluate MI in EC via TVS in order to achieve an improvement in diagnostic accuracy. [30][31][32] Xholi et al 31 the process under control after reaching this competence. Therefore, they conclude that 30-40 cases would be needed to obtain optimal skills in determining myometrial infiltration.…”
Section: Interpretation Of Findings In Clinical Contextmentioning
confidence: 99%